FACTORS AFFECTING OPEN UNEMPLOYMENT RATE IN BANTEN PROVINCE USING PANEL DATA REGRESSION - Annisa Qurrota Ayu (Journal of Mathematics and Mathematics Education, 2024)
Unemployment is a common problem faced by developing countries such as Indonesia. In 2022-2023 Banten Province ranked first in the percentage of the highest Open Unemployment Rate (OUR) in Indonesia. Thus, further research is needed on what factors affect the Open Unemployment Rate (OUR) in Banten Province. This study aims to analyze the influence of average years of schooling (?1), district/city minimum wage (?2), labor force participation rate (?3), and GRDP growth rate (?4) on the Open Unemployment Rate (OUR) in Banten Province in 2013-2022. The analysis method used in this research is panel data regression. The results of this study indicate that the best model selected after going through the Chow test and Hausman test is the fixed effect model. The final result shows that the average years of schooling (?1) has a negative and significant effect on the percentage of Open Unemployment Rate (OUP) in Banten Province, the district/city minimum wage (?2) has a positive and significant effect on the percentage of Open Unemployment Rate (OUP) in Banten Province, labor force participation rate (?3) has a negative and significant effect on the percentage of Open Unemployment Rate (OUP) in Banten Province, and GRDP growth rate (?4) has a negative and significant effect on the percentage of Open Unemployment Rate (OUP) in Banten Province.